2012
DOI: 10.1371/journal.pone.0032568
|View full text |Cite
|
Sign up to set email alerts
|

Uptake Mechanism of ApoE-Modified Nanoparticles on Brain Capillary Endothelial Cells as a Blood-Brain Barrier Model

Abstract: BackgroundThe blood-brain barrier (BBB) represents an insurmountable obstacle for most drugs thus obstructing an effective treatment of many brain diseases. One solution for overcoming this barrier is a transport by binding of these drugs to surface-modified nanoparticles. Especially apolipoprotein E (ApoE) appears to play a major role in the nanoparticle-mediated drug transport across the BBB. However, at present the underlying mechanism is incompletely understood.Methodology/Principal FindingsIn this study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
157
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(172 citation statements)
references
References 53 publications
7
157
0
Order By: Relevance
“…8,9 Nevertheless, the modification of nanoparticles, for example, with apolipoprotein E (ApoE), appears promising for overcoming this problem. 10 Other approaches include the transport of methylprednisolone to glial cells via surface-engineered carboxymethylchitosan/ polyamidoamine (CMCht/PAMAM) dendrimers 11 or the treatment of brain gliomas with a pH-sensitive, dual targeting drug delivery system based on a complex assembly of PAMAM, transferrin, doxorubicin, and tamoxifen. 9 Besides particulate systems, surface modifications and 3D matrices of synthetic dendrimers and polymers were applied to promote neuronal cell adhesion and growth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…8,9 Nevertheless, the modification of nanoparticles, for example, with apolipoprotein E (ApoE), appears promising for overcoming this problem. 10 Other approaches include the transport of methylprednisolone to glial cells via surface-engineered carboxymethylchitosan/ polyamidoamine (CMCht/PAMAM) dendrimers 11 or the treatment of brain gliomas with a pH-sensitive, dual targeting drug delivery system based on a complex assembly of PAMAM, transferrin, doxorubicin, and tamoxifen. 9 Besides particulate systems, surface modifications and 3D matrices of synthetic dendrimers and polymers were applied to promote neuronal cell adhesion and growth.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For instance, the transferrin receptor is abundant in brain capillary endothelium, and it has been reported that coupling nanoparticles to transferrin can aid nanoparticle penetration into the BBB through the transferrin receptor mediated pathway. 16,24 Apolipoprotein E is an endogenous protein involved in the trafficking of naturally occurring LDL particles and when grafted on nanoparticles was reported to enhance BBB penetration, [25][26][27][28][29][30] though not necessarily translocation. 9 Similarly, cationised serum albumin has been reported to cross the BBB by absorptive-mediated trancytosis 1,31 and could also be used to gain nanoparticle access to the brain.…”
Section: Introductionmentioning
confidence: 99%
“…A catalogue of potential BBB-crossing peptides and proteins for functionalization is available (Van et al, 2012) (Spencer and Verma, 2007b); ApoE (Re et al, 2011;Wagner et al, 2012) and Apo A-I (Fioravanti et al, 2012;Kratzer et al, 2007), have been already used to functionalize diverse types of drugs and nanoparticles to allow or enhance BBB crossing. Others, such as Kunitzderived peptides (Angiopeps), presented in plain protein-drug complexes, have entered…”
mentioning
confidence: 99%